Corporations and the State: Emerging of the Problem of Corporate Liability - Shashkova, Anna (Opción, 2019)
The aim of the present article is to find the root of the problem of interaction between the state and corporations. The core part of the research is dedicated to the analysis of emerging of the corporate liability based on the dialectical method of cognition political, legal and socio-economic processes. As a result, the roots of the problem of criminal liability of corporations are purely political. The question on emerging of corporate liability is analysed from a political point of view coming to a conclusion that at present the Russian Federation political conditions are not set in for the matter.